22.3k views
3 votes
F(1)=2 f(n) =3×f(n-1)​

2 Answers

3 votes

If f(n) = -2f(n-1), and you need to evaluate f(5), then we need to look at the the function like this.

f(5) = -2f(4)

f(4) = -2f(3)

f(3) = -2f(2)

f(2) = -2f(1)

Now, let's work this from the bottom up

f(2) = -2f(1) = -2(3) = -6 since we are told that f(1) = 3

f(3) = -2f(2) = -2(-6) = 12

f(4) = -2f(3) = -2(12) =-24

f(5) = -2f(4) = -2(-24) = 48

Hope this helps.

User Pandit Biradar
by
5.2k points
2 votes

The answer would be 7. I just answered this

User Antara Datta
by
4.6k points